STRUCTURAL FEATURES OF COMPOSITIONAL AND SPEECH FORMS IN SCIENTIFIC AND TECHNICAL ARTICLES - Доронкина, Надежда (SWorldJournal, 2020)
between traditional, integrate, and inhomogeneous types. The ways of integration are described. The parts of integration can be forms of both the same and different types. It was revealed that there are two types inhomogenuity in the texts of technical re